CALCULATION OF DEFORMATION DURING BENDING OF THE EXCHANGEABLE ELEMENT IN THE WORKING ZONE OF THE COLUMN IN THE SAWING MACHINE - Ergashev , Ilhom Olimzhanovich (Educational Research in Universal Sciences, 2023)
In this article, the value of the force required to bend the exchanger elements of the chain saw gin in the desired radius is calculated theoretically and compared with the value determined based on experience. Taking into account the elastic deformation of the material during the bending process, the return value of the material was calculated and the numerical values ​​of the stresses required during the bending process were determined.